Selective Fermentation of Lactobacillus and Streptococcus In Vitro: Effects of Chinese Fermented Glutinous Rice on the Growth Promotion of Potential Probiotics. (23rd December 2021) - Ma, Wenliang; Ni, Xiao; Guo, Ying; Zhang, Yu; Zhu, Chaojie; Li, Yinping; Shen, Chi; Yuan, Biao; Xu, Xiao
Abstract : A functional Chinese fermented glutinous rice has been developed with the supplementation of Fu brick tea (CRW-FBT). In this study, we aimed to evaluate its effect on the growth of potential probiotic strains in the Lactobacillus, Streptococcus, and Weissella genus, compared with traditional Chinese fermented glutinous rice (CRW). The growth profiles of lactic acid bacteria were analyzed based on fermentations in vitro, and the optical densities were recorded at 600 nm during the whole fermentation. Growth curve, maximum OD600 nm, and growth rate were measured and compared among samples with different ratios of CRW-FBT and CRW addition. Through the multiple analysis of growth parameters, we found that all the tested strains obtained better growth results when CRW-FBT was supplemented to the media, compared with the CRW and basic media. The bacterial growth was promoted by exhibiting the shortened lag time, prolonged logarithmic phase and stationary phase, and increased growth rate and cell density, as well as the better performance after 24 h and 48 h fermentation. Besides, short-chain fatty acids and organic acids in CRW-FBT were founded. Our work demonstrated the positive effect of Fu brick tea supplemented in the CRW and illustrated its beneficial role in the food fermentation industry for the purpose of microorganism enrichment and the improvement of microbial metabolism.